A review on distillate water quality parameter analysis in solar still. Issue 11 (18th August 2021) - Arunkumar, T.; Raj, Kaiwalya; Chaturvedi, Meenakshi; Thenmozhi, A.; Denkenberger, D.; Tingting, Guo
ABSTRACT: In this review, desalinated water quality analysis in various solar stills are examined. Many authors have performed experiments in solar stills along with the testing of physical and chemical water quality examinations for feed water and desalinated water. This was performed on different types of feed water, namely, ocean water, bore well water, water from lakes, tap water and synthetic water from the laboratory are investigated. This research is important to understand solar still performance for a variety of different water types. Based on the investigation, the pH and TDS value (before & after treatment) of the synthetic water, brackish water, ground water, lake water and sea water are improved and is compliant with WHO-2017 and BIS-2010 water quality standards. Water quality results of dissolved macro minerals (before & after treatment) in the water are reviewed and useful conclusions are drawn.